Activated Polyhydroxyalkanoate Meshes Prevent Bacterial Adhesion and Biofilm Development in Regenerative Medicine Applications - Piarali, Sheila; Marlinghaus, Lennart; Viebahn, Richard; Lewis, Helen; Ryadnov, Maxim G.; Groll, Jürgen; Salber, Jochen; Roy, Ipsita (Frontiers in Bioengineering and Biotechnology, 2020)
Regenerative medicine has become an extremely valuable tool offering an alternative to conventional therapies for the repair and regeneration of tissues. The re-establishment of tissue and organ functions can be carried out by tissue engineering strategies or by using medical devices such as implants. However, with any material being implanted inside the human body, one of the conundrums that remains is the ease with which these materials can get contaminated by bacteria. Bacterial adhesion leads to the formation of mature, alive and complex three-dimensional biofilm structures, further infection of surrounding tissues and consequent development of complicated chronic infections. Hence, novel tissue engineering strategies delivering biofilm-targeted therapies while at the same time allowing tissue formation are highly relevant. In this study our aim was to develop surface modified polyhydroxyalkanoate-based fiber meshes with enhanced bacterial anti-adhesive and juvenile biofilm disrupting properties for tissue regeneration purposes. Using reactive and amphiphilic star-shaped macromolecules as an additive to a polyhydroxyalkanoate spinning solution, a synthetic antimicrobial peptide, Amhelin, with strong bactericidal and anti-biofilm properties, and Dispersin B, an enzyme promoting the disruption of exopolysaccharides found in the biofilm matrix, were covalently conjugated to the fibers by addition to the solution before the spinning process. Staphylococcus epidermidis is one of the most problematic pathogens responsible for tissue-related infections. The initial antibacterial screening showed that Amhelin proved to be strongly bactericidal at 12 µg/ml and caused >50% reductions of biofilm formation at 6 µg/ml, while Dispersin B was found to disperse >70% of pre-formed biofilms at 3 µg/ml. Regarding the cytotoxicity of the agents towards L929 murine fibroblasts, a CC50 of 140 µg/ml and 115 µg/ml was measured for Amhelin and Dispersin B, respectively. Optimization of the electrospinning process resulted in aligned fibers. Surface activated fibers with Amhelin and Dispersin B resulted in 88% reduction of adhered bacteria on the surface of the fibers. Additionally, the materials developed were found to be cytocompatible towards L929 murine fibroblasts. The strategy reported in this preliminary study suggests an alternative approach to prevent bacterial adhesion and, in turn biofilm formation, in materials used in regenerative medicine applications such as tissue engineering.